CELAS E ELAS: a rescue of the memories of the experience felt in the female prison spaces of Joinville Regional Prison (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This text narrates the experience of a feminist photographer in the project [Celas] e Elas: [des]montagem teatral sobre mulheres e cárceres. The theatrical project was realized in 2019 by Daiane Dordete and Samira Sinara with inmates of the Regional Prison of Joinville, with support from the Sistema Municipal de Desenvolvimento pela Cultura - SIMDEC/2016. It was produced by Cia VAi! - Núcleo de Pesquisa em Artes Cênicas (Joinville/SC). The exhibition  “Para além das celas” was produced with photographs made by Jéssica Michels, during the theater workshops with inmates of the Regional Prison of Joinville through a project called Teatro com mulheres em privação de liberdade. This text takes the liberty of being written in such a way as to be a fluid and authentic account of a photographic experience with prisonersin the female prison system in the city of Joinville.
Keywords: Female prison; Photography; Joinville Regional Prison